CHILD PROTECTION IN CUSTODY (HADHANAH) FOLLOWING PARENTAL DIVORCE - Siti Nurheliza; Faisar Ananda (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
Divorce often raises various issues that impact the fulfillment of children's rights, particularly regarding care, maintenance, and legal protection. This study aims to analyze the concept of hadhanah in Islamic law, parental responsibilities towards children after divorce, and the legal consequences for parents who fail to fulfill their obligations. The method used is normative legal research with a statutory and conceptual approach. The research data was obtained through a literature review covering primary and secondary legal materials. The results indicate that hadhanah is an obligation to care for, educate, and protect children for the sake of their well-being. Divorce does not eliminate parental responsibility towards children, either in the form of care or provision. Islamic law and Indonesian positive law both place the best interests of the child as the primary basis for determining custody. Parents who neglect their obligations towards their children may be subject to legal consequences in accordance with applicable regulations. Child protection after divorce requires commitment and responsibility from both parents to ensure the optimal fulfillment of children's rights.